Adenylyl cyclase 4 does not regulate collecting duct water and sodium handling - Kittikulsuth, Wararat (Wiley Periodicals, Inc., 2014)
Adenylyl cyclase (AC)‐stimulated cAMP is a key mediator of collecting duct (CD) Na and water transport. AC isoforms 3, 4, and 6 are expressed in the CD. Our group demonstrated that AC6, but not AC3, is involved in regulating CD Na and water transport. However, the role of AC4 in such regulation remains unknown. Therefore, we generated mice with loxP‐flanked critical exons in the Adcy4 gene and bred with mice expressing the aquaporin‐2/Cre recombinase transgene to yield CD principal cell‐specific knockout of AC4 (CD AC4 KO). Isolated inner medullary CD showed 100% genomic target gene recombination in CD AC4 KO mice, while microdissected cortical CD and renal papillary AC4 mRNA was significantly reduced in CD AC4 KO mice. CD AC4 KO had no effect on vasopressin (AVP)‐stimulated cAMP generation in the inner medulla. Water intake, urine volume, and urine osmolality were similar between CD AC4 KO and control mice during normal or restricted water intake. Sodium intake, urinary Na excretion, and blood pressure on a normal‐, high‐, or low‐Na diet were not affected by CD AC4 KO. Moreover, there were no differences in plasma AVP or plasma renin concentration between CD AC4 KO and control mice. In summary, these data suggest that CD AC4 does not play a role in the physiologic regulation of CD Na and water handling.